Top 3 Differentials in Gastrointestinal Imaging A Case Review - Saenz, Rocky, 1973- (Thieme Medical Publishing Inc., 2019)
The highest-yield, most complete gastrointestinal radiology exam prep and learning tool available today! Top 3 Differentials in Gastrointestinal Imaging: A Case Review by renowned radiologist Rocky C. Saenz and esteemed colleagues is one in a series of radiology case books mirroring the highly acclaimed O'Brien classic, Top 3 Differentials in Radiology. The book is organized into five abdominal imaging sections covering hepatobiliary, pancreas and spleen, gastrointestinal (GI) tract, mesentery and vascular, and abdominal wall. Each case is formatted as a two-page unit. The left page features clinical images, succinctly captioned findings, and pertinent clinical history. The right page includes the key imaging gamut, differential diagnoses rank-ordered by the "Top 3," additional diagnostic considerations, and clinical pearls. Each section has multiple differential-based cases and some of them include important "Roentgen Classics" cases with imaging findings characteristic of a single diagnosis